2023
DOI: 10.1021/acssuschemeng.2c07495
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting Ancient Roman Cement: The Environmental-Friendly Cementitious Material Using Calcium Hydroxide-Sodium Sulfate-Calcined Clay

Abstract: This study proposes an environmental-friendly cementitious material using calcium hydroxide-sodium sulfatecalcined clay based on the idea of ancient Roman cement. The pozzolanic reaction characteristics of calcined clay are studied by adjusting the ratio of calcined clay and calcium hydroxide in both experimental and thermodynamic modeling methods, which demonstrate that 70% calcined clay and 30% calcium hydroxide are the optimal ratio for the pozzolanic reaction of calcined clay to promote the formation of hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Inspiration in designing novel sustainable materials with enhanced properties can also come from ancient civilizations and cultures, where nanomaterials and interfacial phenomena were exploited based on empirical knowledge. Examples include archeological or paleontological materials that survived to recent times, or the enhanced properties of Maya plasters (that mixed biomacromolecules in calcium carbonate biominerals) and Roman cement . With today’s awareness and scientific understanding of colloidal and interfacial processes, the time thus is ripe for a new, sustainable breakthrough in the preservation of works of art.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Inspiration in designing novel sustainable materials with enhanced properties can also come from ancient civilizations and cultures, where nanomaterials and interfacial phenomena were exploited based on empirical knowledge. Examples include archeological or paleontological materials that survived to recent times, or the enhanced properties of Maya plasters (that mixed biomacromolecules in calcium carbonate biominerals) and Roman cement . With today’s awareness and scientific understanding of colloidal and interfacial processes, the time thus is ripe for a new, sustainable breakthrough in the preservation of works of art.…”
Section: Discussionmentioning
confidence: 99%
“…Examples include archeological or paleontological materials that survived to recent times, 136 or the enhanced properties of Maya plasters (that mixed biomacromolecules in calcium carbonate biominerals) 137 and Roman cement. 138 With today’s awareness and scientific understanding of colloidal and interfacial processes, the time thus is ripe for a new, sustainable breakthrough in the preservation of works of art.…”
Section: Discussionmentioning
confidence: 99%
“…Nowadays, the replacement of cement clinker by activator combined supplementary cementitious materials (Slag, fly ash, calcined clay, etc.) has become a significant direction for low-carbon cement. Limestone and CaO are widely used and accepted as integral components for their various sources. ,,,, However, the lack of an alkaline environment and early mechanical property development limit its large-scale application. The frequently used NaOH and NaSiO 3 combined with slag, fly ash, and other solid wastes have good strength development, but their high alkalinity and cost have yet to be effectively solved. , Many studies have shown that Ca­(OH) 2 and CaO are potential alternatives, ,, for the bulk cost of NaOH is approximately 5–6 times higher than that of CaO .…”
Section: Introductionmentioning
confidence: 99%